Regioselective Synthesis of N-β-Hydroxyethylaziridines by the Ring Opening Reaction of Epoxides with Aziridine Generated In Situ - Kim, Ha Young (2006)
[Image: see text] Biologically important N-β-hydroxyethylaziridine intermediates were conveniently prepared by regioselective ring opening reactions of diversely substituted epoxides. Ethyleneimine generated in situ under basic conditions from β-chloroethylamine was used as a nucleophile to open the epoxides in an aqueous environment.